ANALISIS KEMISKINAN, KETIMPANGAN, DAN PENGANGGURAN TERHADAP IPM DI 3 PROVINSI SUMATERA MENGGUNAKAN SPLINE TRUNCATED - Lutfiah Firlian; Idhia Sriliana; Della Nur Afni; Ukasyah Aflah; Pepi Novianti (Jurnal Gaussian, 2025)
This study aims to analyze the effect of the open unemployment rate (TPT), economic inequality (Gini ratio), and the percentage of poor people on the Human Development Index (HDI) in three provinces with the highest poverty rates on Sumatra Island, namely Aceh, Bengkulu, and South Sumatra. The truncated spline nonparametric regression method was used in this study to accommodate the complex relationship between variables without assuming a particular distribution. The results of the analysis show that all three independent variables have an effect. The results of the analysis show that the best model is obtained with four knot points, producing a minimum Generalized Cross Validation (GCV) value of 7,9580594, a minimum Mean Squared Error (MSE) value of 3.899, and a coefficient of determination (R²) of 77,96%. With a fairly high level of accuracy, this model can be used as a basis for further analysis in understanding the relationship between economic variables and the HDI. In addition, this model can be a reference in formulating more effective policies to reduce economic inequality and improve the welfare of people in the poorest areas on Sumatra Island.